2008
DOI: 10.1111/j.1468-1331.2008.02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure is not associated with haematoma enlargement in acute intracerebral haemorrhage

Abstract: In an exploratory analysis, we did not find an association between BP and HE within the first 24 h after an acute ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Some investigators report a possible association between elevated blood pressure and hematoma enlargement415. However, the association has not been established in other studies1617. In line with these latter studies, we found that neither history of hypertension nor blood pressure are associated with early hematoma expansion.…”
Section: Discussionsupporting
confidence: 79%
“…Some investigators report a possible association between elevated blood pressure and hematoma enlargement415. However, the association has not been established in other studies1617. In line with these latter studies, we found that neither history of hypertension nor blood pressure are associated with early hematoma expansion.…”
Section: Discussionsupporting
confidence: 79%
“…Stroke patients were examined noninvasively and repeatedly at the bedside. In the acute phase of cerebral hemorrhage, hematoma enlargement has been observed in 4.3–45% patients 21–23 . With TCCS, one should be able to evaluate hematoma enlargement at the bedside 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of an acute hemorrhagic stroke, elevated blood pressure may correlate with hematoma size (10,11). The wide practice of palliation rather than aggressive early blood pressure control is thought to contribute in part to the high morbidity and mortality of ICH compared to other forms of stroke.…”
mentioning
confidence: 99%